Media Coverage of Sports Issues in Libya: A Field Study – Libya Sports Channel as a Case Study (Al-Farooq Journal of Sciences, 2026)
This field study aims to evaluate the Libyan Sports Channel's coverage of sports issues from the perspective of its Libyan audience, and to reveal the impact of this coverage on their attitudes and the extent to which their media needs are met. This is particularly relevant given the challenges facing the Libyan sports scene, including a lack of diversity in programming and occasional absence of objectivity in addressing sensitive issues. Furthermore, the scarcity of field studies measuring viewers' opinions and impressions of the channel's performance presents a significant research challenge. The researcher formulated a central question regarding the Libyan audience's evaluation of this coverage and its effectiveness in fulfilling their expectations. This question led to specific objectives, including identifying the extent of the channel's viewership, the most important issues it addresses, the motivations behind audience viewership, the types of programs viewers prefer, their sports priorities, and their opinions on the quality of the media coverage provided. To achieve these objectives, the researcher adopted a descriptive approach using a field survey methodology, employing a questionnaire as the primary data collection tool. The study was conducted on a simple random sample of 384 respondents from the channel's audience in the cities of Tripoli and Janzour. The data were statistically analyzed using SPSS software, within the framework of the uses and gratifications theory, which posits that audiences actively choose media outlets to meet their needs. The results revealed that the average daily viewing time was less than one hour for 50.7% of respondents, with the "Premier League Studio" program being the most watched at 57.4%. The results also showed that the most prominent motivation for watching was the channel's coverage of issues of interest to the sports audience. Furthermore, the results indicated that the channel utilized its media expertise to some extent in addressing these issues, with 52.7% of respondents finding it helpful. Regarding the most important issues raised by the channel, the successes and failures of sports federations ranked first. The results also showed that 85.8% of respondents believe the channel focuses on covering local events, while its coverage of Arab and international events is weak. The study revealed shortcomings in the channel's performance, namely a lack of credibility and professionalism.
Keywords: Media coverage, sports issues, Libya Sports Channel, sports media, Libyan sports audience.